Ketahanan Destinasi Pariwisata Desa Jungut Batu Kecamatan Nusa Penida - Daneshwara Cakraverthi Sedana; Hanugerah Kristiono Liestiandre; Hartanti Woro Susianti (JURNAL KEPARIWISATAAN, 2023)
Tourism Destination Resilience (TDR) is a process and outcome that enables a tourism destination to survive adversity and rise from a crisis or disaster. One of the tourist destinations with serious risks related to emergencies and disasters is Jungut Batu Village. The problems faced by Jungut Batu Village are very complex, starting from its geographical location and the social life of the people to its community's excessive dependence on tourism. This study examines the resilience of tourist destinations in Jungut Batu Village. This study's qualitative data type is collected through interviews, observations, and documentation. The informant determination technique used was purposive sampling and snowball sampling techniques, with the criterion that the informant must be a person or stakeholder who is knowledgeable or has accurate information about tourism destinations in Jungut Batu village and has an important role. Then, the collected data was descriptively and qualitatively analyzed using ten destination resilience stages initiated by PATA 2020. The results showed that Jungut Batu Village had fulfilled every criterion of the ten destination resilience stages proposed by PATA 2020. I am running a few minutes late; my previous meeting is over. And, therefore, was classified as a resilient tourismÂ destination.